2009
DOI: 10.1007/s10344-009-0281-4
|View full text |Cite
|
Sign up to set email alerts
|

Feeding activity and dietary composition of roe deer at the southern edge of their range

Abstract: We studied feeding activity and dietary components of hand-reared European roe deer (Capreolus capreolus) in Israel. Our ultimate goal was to assess habitat suitability for future reintroduction of the species, which has been locally extinct for nearly a century. Activity patterns, diet composition, and body mass of four does were monitored in two (fenced) typical east Mediterranean habitats: mature forest and scrubland recovering from fire. Food supplements were provided between trials. Throughout the year, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…It is commonly recognized as a browser, but it can exploit a large number of plant species, adapting its dietary niche to the spatiotemporal variation of food availability (e.g., Tixier and Duncan 1996;Duncan et al 1998;Wallach et al 2010;Minder 2012). In open and agricultural systems, the roe deer can become a grazer and it can feed largely on grass (e.g., Minder 2012).…”
Section: Discussionmentioning
confidence: 98%
“…It is commonly recognized as a browser, but it can exploit a large number of plant species, adapting its dietary niche to the spatiotemporal variation of food availability (e.g., Tixier and Duncan 1996;Duncan et al 1998;Wallach et al 2010;Minder 2012). In open and agricultural systems, the roe deer can become a grazer and it can feed largely on grass (e.g., Minder 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The identification of fruits (Rosaceae) in faeces further confirms that these cervids seek out more palatable and high-quality food sources. Previous studies (Tixier et al 1997;Wallach et al 2010) have shown that fruits are the most preferred food items in some seasons. In particular, Wallach et al (2010) found that fruits were the dominant portion of roe deer diet in summer and early autumn.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies (Tixier et al 1997;Wallach et al 2010) have shown that fruits are the most preferred food items in some seasons. In particular, Wallach et al (2010) found that fruits were the dominant portion of roe deer diet in summer and early autumn. According to these authors, this feeding strategy demonstrates that roe deer can also exhibit opportunistic behaviour in some circumstances.…”
Section: Discussionmentioning
confidence: 98%
“…will suffer from a decreased dispersal rate) than that of generalists (Devictor, Julliard & Jiguet, 2008). For example, the generalist roe deer (Wallach, Shanas & Inbar, 2010) can cope with a fragmented landscape because of its plastic feeding patterns (Abbas et al, 2011), whereas a specialist deer, the white-lipped deer, becomes vulnerable due to fragmentation processes (Leslie, 2010). A study of two gecko species from eucalyptus forests in Australia showed that the specialist Oedura reticulata failed to form a meta-population structure whereas the generalist Gehyra variegata maintained a widespread distribution through meta-population dynamic (Sarre, Smith & Meyers, 1995;Hoehn, Sarre & Henle, 2007).…”
Section: Introductionmentioning
confidence: 99%